Implementation of Personal Selling and Direct Marketing in Increasing Sales Turnover at Agency Centre HNI Cianjur - Hegiarto, Aldy Santo; Sapitri, Rani (LPPPIPublishing, 2024)
Marketing strategy is one of the company's tools for achieving marketing goals. Many marketing strategies that can be used, but whether these strategies are appropriate and effective for increasing sales turnover or not. This research aims to determine the effectiveness of implementing personal selling and direct marketing strategies in increasing sales turnover at the AC HNI Cianjur. The data used in this research are primary data and secondary data, with data collection techniques through interviews, observation and documentation. Meanwhile, this type of research uses a qualitative approach, with descriptive data analysis techniques. The results of this research are that direct marketing strategies are more effective in increasing sales turnover, but it turns out that personal selling also plays an active role in obtaining this turnover. It turns out that in this research there are aspects that show that apart from personal selling and direct marketing, there are many ways and strategies to increase sales turnover, but in this research, the researchers only focused on personal selling and direct marketing strategies.